From revolution to war : state relations in a world of change - Conge, Patrick J., 1951- (University of Michigan Press, 1996)
In the history of international relations few events command as much attention as revolution and war. As separate occurrences, each is an example of the human capacity for destruction and renewal. Together, revolution and war are potentially cataclysmic in human terms. Over the centuries, revolutionary transformations produced some of the most ruinous and bloody wars. Nevertheless, the breakdown of peace in time of revolution is poorly understood. Patrick Conge offers a groundbreaking study of the relationship between war and revolution. Conditions that lead to and sustain wars in general are identified and placed in the light of revolutionary transformations. Once the argument is presented, historical case studies are used to test plausibility. Conge demonstrates the importance of the effect of revolutionary organization and ideas on the outcome of conflicts.